2010
DOI: 10.1177/0146167209359701
|View full text |Cite
|
Sign up to set email alerts
|

Causal Uncertainty and Psychological Well-Being: The Moderating Role of Accommodation (Secondary Control)

Abstract: Causal uncertainty about one's own outcomes (CU-Own) is associated with negative affect, depression, and a lack of perceived primary control. We predicted that accommodation, or secondary control, would act as a psychological buffer for high-CU-Own individuals, reducing negative affect and depression.We tested this hypothesis in two studies: one cross-sectional (Study 1) and one longitudinal (Study 2). Participants completed measures of CU-Own, harmony control, and depression in Study 1 and measures of CU-Own,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 29 publications
2
29
0
2
Order By: Relevance
“…If individuals are able to accept and adjust themselves to their uncertainty and salient negative events, it should be easier for them to disengage from endless rumination about the causes of those events, and thereby escape the negative affect that can stem from unsuccessful uncertainty reduction efforts. Consistent with this idea, Tobin and Raymundo (2010) found that although higher levels of chronic causal uncertainty predicted increasing negative affect over time when secondary control was low, this was not the case when secondary control was high.…”
Section: Causal Uncertaintymentioning
confidence: 73%
See 3 more Smart Citations
“…If individuals are able to accept and adjust themselves to their uncertainty and salient negative events, it should be easier for them to disengage from endless rumination about the causes of those events, and thereby escape the negative affect that can stem from unsuccessful uncertainty reduction efforts. Consistent with this idea, Tobin and Raymundo (2010) found that although higher levels of chronic causal uncertainty predicted increasing negative affect over time when secondary control was low, this was not the case when secondary control was high.…”
Section: Causal Uncertaintymentioning
confidence: 73%
“…Prior research has focused primarily on affect as an outcome of secondary control (Chipperfield et al, 2012;Morling & Evered, 2006;Tobin & Raymundo, 2010). Of interest in the current research is whether affect can influence secondary control.…”
Section: Increasing Secondary Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Belirsizliğin özel bir durumunu inceleyen nedensel belirsizlik kuramı (Causal Uncertainty Theory) (Weary ve Edwards, 1994, 1996 kişilerin neden sonuç ilişkisini atfedebilme becerisinden şüphe etmesi ile ilgilenmektedir. Çalışmaların sonuçlarına göre nedensel belirsizlik ile olumsuz duygu durumu (Tobin ve Raymundo, 2010), depresyon (Weary ve Edwards, 1994;1996), nörotiklik (Edwards, Weary ve Reich, 1998) ve onay arama ihtiyacı (Jacobson ve Weary, 1999;Jacobson, 2007) (Hogg, 2009;Hogg ve Abrams, 1993). Gruplar kişiye hem kendini ve iç grup üyelerini tanımlaması hem de kendini dış grup üyelerinden ayrıştırması için fırsat sunar (Hogg, 2009).…”
Section: Belirsizliğin Etkileri Nelerdir?unclassified